Detecting the phenomenon of transferring the impact of the training process from physical variables to shooting skill - DJAMEl EDDINE, RECHAM (International Journal of Psychosocial Rehabilitation, 2022)
The study aims to reveal the phenomenon of transferring the impact of the training process from physical variables to the skill of shooting ,This study included 16 players from the amateur sports club "Amal Al-Hashemiah" ASC EL, As a sample for the study, the researcher used circuit training program, physical tests and a test of shooting , The statistical package spss program was also used to analyze the results of the study.Finally, it was found that there is a direct correlation between the physical variables for the purpose of the study and the skill of shooting. Through the results, the researcher came to prove the transmission of the effect of training and Demonstrate the transfer of the effect of training from the physical attributes of speed and force to the skill of shooting .